2007
DOI: 10.1016/j.schres.2007.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Facial emotion recognition in schizophrenia:When and why does it go awry?

Abstract: Objective-Schizophrenia patients demonstrate impaired emotional processing that may be due, in part, to impaired facial emotion recognition. This study examined event-related potential (ERP) responses to emotional faces in schizophrenia patients and controls to determine when, in the temporal processing stream, patient abnormalities occur.Method-16 patients and 16 healthy control participants performed a facial emotion recognition task. Very sad, somewhat sad, neutral, somewhat happy, and very happy faces were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
170
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(198 citation statements)
references
References 61 publications
(61 reference statements)
16
170
2
Order By: Relevance
“…These regions reportedly play a critical role in visual processes such as motion discrimination , face processing (Puce et al, 1995;Narumoto et al, 2000), and reading (Pugh et al, 1996;Booth et al, 2001), all of which have been shown to be impaired in schizophrenia (Chen et al, 1999a(Chen et al, , 2004Manor et al, 1999;Herrmann et al, 2004;Revheim et al, 2006;Turetsky et al, 2007). Together, our findings thus suggest that the deficient responsiveness of the magnocellular pathways in schizophrenia patients may influence the operation of higherorder perceptual and cognitive systems.…”
Section: Discussionmentioning
confidence: 52%
“…These regions reportedly play a critical role in visual processes such as motion discrimination , face processing (Puce et al, 1995;Narumoto et al, 2000), and reading (Pugh et al, 1996;Booth et al, 2001), all of which have been shown to be impaired in schizophrenia (Chen et al, 1999a(Chen et al, , 2004Manor et al, 1999;Herrmann et al, 2004;Revheim et al, 2006;Turetsky et al, 2007). Together, our findings thus suggest that the deficient responsiveness of the magnocellular pathways in schizophrenia patients may influence the operation of higherorder perceptual and cognitive systems.…”
Section: Discussionmentioning
confidence: 52%
“…People with severe psychiatric disorders, such as schizophrenia, were characterized by impaired neural activity in response to BSF faces (Couture, Penn, & Roberts, 2006;Lee, Kim, Kim, & Bae, 2010;Turetsky et al, 2007). We did not expect that level of neural impairment in a normal population.…”
Section: The Present Studymentioning
confidence: 93%
“…Participants were not told to fixate on the cross when it appeared, thus making the prompt a passive intervention. The three-second prompt time was selected based on research that problems in emotion perception occur early in the perceptual process (Gordon et al, 1992;Swartz et al, 1999;Turetsky et al, 2007). In the shaping condition, if the participant correctly identified the emotional expression, they were reinforced with ten cents that was placed in a cup in front of the participant; incorrect responses were not reinforced .…”
Section: Intervention Conditions and Proceduresmentioning
confidence: 99%